Konsep Keadilan Dalam Poligami (Sebuah Kajian Yuridis) - Pancasilawati, Abnan (FENOMENA, 2013)
The concept of justice is a fundamental debate and is always actual throughout the life of humankind. Justice, in the history of human thought, began since the era of Socrates, Plato, and Aristotle. The concept or justice theorizing is still actual, not final yet, until nowadays. It is caused by its characteristics which are abstract and so meaningful. Therefore, it needs justice theorizing to find a comprehensive understanding about justice in order to find out components contained in it through research activity. One of the law purposes is justice. It needs law instruments to meet the law purpose such as Legislation, legal weight, customary law, canon law, and many others. All the law instruments can rule specific things such as provisions in the field of family law. Polygamy is a controversial problem whereby in its debate emerges various opinions primarily on the justice concept as the main requirement in polygamy. Some scholars interpret that justice in polygamy merely deals with material aspect. However, some others interpret that justice in polygamy covers the aspects of material and immaterial (love and compassion).